2020
DOI: 10.1111/jcmm.16220
|View full text |Cite
|
Sign up to set email alerts
|

Rea regulates microglial polarization and attenuates neuronal apoptosis via inhibition of the NF‐κB and MAPK signalings for spinal cord injury repair

Abstract: Inflammation and neuronal apoptosis aggravate the secondary damage after spinal cord injury (SCI). Rehmannioside A (Rea) is a bioactive herbal extract isolated from Rehmanniae radix with low toxicity and neuroprotection effects. Rea treatment inhibited the release of pro‐inflammatory mediators from microglial cells, and promoted M2 polarization in vitro, which in turn protected the co‐cultured neurons from apoptosis via suppression of the NF‐κB and MAPK signalling pathways. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…A large number of studies have shown that reducing central nervous system inflammation and peripheral inflammatory cell infiltration (e.g., macrophage) can significantly reduce secondary damage and promote functional recovery following SCI [16, 43]. After SCI, microglia/macrophages not only polarize into M1 cells causing inflammation, but they may also partially polarize into M2 cells, which have anti-inflammatory properties [5, 54]. The polarized orientation of microglia/macrophages after SCI is strongly skewed toward the M1 phenotype [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have shown that reducing central nervous system inflammation and peripheral inflammatory cell infiltration (e.g., macrophage) can significantly reduce secondary damage and promote functional recovery following SCI [16, 43]. After SCI, microglia/macrophages not only polarize into M1 cells causing inflammation, but they may also partially polarize into M2 cells, which have anti-inflammatory properties [5, 54]. The polarized orientation of microglia/macrophages after SCI is strongly skewed toward the M1 phenotype [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no effective treatments for SCI. The pathological process of SCI can be divided into primary and secondary injuries [4,5]. Primary SCI, which includes in situ structural damage, vascular rupture in the lesion area, and local bleeding around the lesion area, is caused by traumatic events (e.g., vehicle accidents or falling from a building) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are the active ingredient extracted from these two Materia Medica, and they are the multi-functional phytochemical presenting substantial characteristics that can be exploited for therapeutic agents targeting on various diseases, pharmaceutically [35]. Xiao et al (2021) found that avonoid-enriched RR extract shown the neuronal protective properties by suppressing of the NF-κB and MAPK signaling pathway [36]. Xie and Du (2011) published the similar results, they found RR methanol extraction shown the therapeutic functions for in ammatory treatment by blocking TNF-α, IL-1β, IL-6 and IL-15 productions [37].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary SCI is caused by pathological changes after primary injury, which can result in inflammation, oxidative stress, glial scar formation, neuronal apoptosis, and neuronal necrosis (Anjum et al, 2020;Wang et al, 2020d). Recently, SCI models induced by lipopolysaccharide (LPS) are widely used to explore SCI pathogenesis and find new therapeutic medicine to treat SCI (Xiao et al, 2021).…”
Section: Spinal Cord Injurymentioning
confidence: 99%